Mapping Research Trends on Organizational Culture Quality Standards: Bibliometric Analysis Using VOSViewer - Jannah, Athohiratul; Siregar, Erliati; Yasnimawati, Yasnimawati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Background. Organizational culture plays a pivotal role in shaping the effectiveness of quality management systems such as ISO 9001 and Total Quality Management (TQM), contributing to sustainable organizational performance. However, recent bibliometric trends suggest a notable decline in scholarly attention to this intersection.Purpose. This study aims to systematically map the current landscape of research on organizational culture and quality standards. Specifically, it seeks to identify publication trends over time, the extent of scholarly collaboration, and emerging thematic clusters through keyword analysis. By doing so, the study addresses a literature gap concerning the lack of recent integrative overviews in this domain.Method. Using a bibliometric approach, 200 scientific publications published between 2000 and 2024 were analyzed. Data were collected from three major databases: Scopus, Dimensions, and Google Scholar. VOSviewer software was employed to visualize co-authorship networks, institutional collaboration, annual publication trends, and keyword co-occurrence. The keyword analysis produced four main thematic clusters representing the dominant research topics in this field.Results. The analysis reveals a consistent decline in the number of publications on organizational culture and quality standards in recent years. Nevertheless, certain themes—such as the integration of organizational culture with ISO 9001 and Total Quality Management (TQM)—remain prevalent. Collaboration between authors and institutions was found to be limited, suggesting fragmented research efforts across regions and disciplines.Conclusion. The findings indicate a need to revitalize academic discourse on organizational culture quality standards, particularly in light of evolving challenges in the global and digital business environment. This study offers valuable insights and serves as a foundation for future research that is more responsive, interdisciplinary, and application-oriented. It also provides practical implications for practitioners seeking to align organizational culture with quality improvement initiatives